Yield And Its Components In Groundnut Under Partial Shade In Coconut Garden - Rajasree MR (Department of Plant Breeding, College of Agriculture, 1988)
A study on the parameters of variability, heritability and genetic advance and correlation of pod yield with other components were undertaken in thirtyone varieties of groundnut to select genotypes having good yield and adaptability under partially shaded conditions of coconut gardens. The study was conducted during kharif 1987 at the Department of Plant Breeding, College of Agriculture, Vellayani, by raising the varieties in a randomised block design with four replications. Analysis of variance revealed significant differences among varieties for the characters like plant height, first date of flowering , flowering duration, pod yield per plant on fresh weight basis, pod number per plant, mature to immature pod ratio, pod yield per plot on fresh and dry weight basis, 100 pod weight, 100 kernel weight, shelling percentage, halum yield per plant and per plot on fresh and dry weight basis, harvest index, photosynthetic efficiency at reproductive phase, leaf area index at reproductive phase and Cercospora leaf spot disease score. Analysis of variance for chlorophyll-a, b and total pigments revealed that there was no significant difference among the varieties with respect to chlorophyll pigment content. Analysis of variance for shade intensity measured in each plot during vegetative and reproductive phase indicated the presence of uniform shade in the experimental field. High genotypic and phenotypic coefficients of variation, heritability and genetic advance were observed for hundred pod weight and mature to immature pod ratio, suggesting the reliability of these characters during the selection programme for the improvement of this crop. Correlation analysis of dry pod yield per plot with twentyfour characters revealed that fresh pod yield per plot, fresh and dry pod yield per plant, pod number per plant, halum yield per plot on fresh and dry weight basis, harvest index and photosynthetic efficiency during reproductive phase showed relatively high genotypic correlation with dry pod yield per plot. The study indicated that for selecting an ideal plant type of groundnut for partially shaded conditions we have to look for the tallest, earliest flowering and vegetatively maximum vigorous individual plant.